2022
DOI: 10.1111/imj.15929
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular disease management in Australian adults with type 2 diabetes: insights from the CAPTURE study

Abstract: BackgroundType 2 diabetes (T2D) is a well‐recognised cardiovascular disease (CVD) risk factor, and recent guidelines for the management of T2D include consideration of CVD risk.AimTo assess whether contemporary clinical management of Australians with T2D is in accord with recent national and international guidelines.MethodsThis Australia‐specific analysis of the CAPTURE study, a non‐interventional, cross‐sectional study included adults diagnosed with T2D ≥180 days prior to providing informed consent and visiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
0
1
Order By: Relevance
“…We found that only 11.65% of eligible patients taking SGLT2i and GLP1RA had received either of these agents by 2020. In contrast to previous studies conducted in the US and Australia, where over 20% of patients with concurrent T2DM and ASCVD were using one of these agents [19,29] it is evident that a substantial number of patients in South Korea did not receive adequate treatment. Furthermore, the utilization of SGLT2i and GLP1RA was signi cantly shorter than that of noncardioprotective antidiabetic agents.…”
Section: Discussioncontrasting
confidence: 74%
“…We found that only 11.65% of eligible patients taking SGLT2i and GLP1RA had received either of these agents by 2020. In contrast to previous studies conducted in the US and Australia, where over 20% of patients with concurrent T2DM and ASCVD were using one of these agents [19,29] it is evident that a substantial number of patients in South Korea did not receive adequate treatment. Furthermore, the utilization of SGLT2i and GLP1RA was signi cantly shorter than that of noncardioprotective antidiabetic agents.…”
Section: Discussioncontrasting
confidence: 74%